The Portrayal of Mortality and Its Impact on Human Behaviour in ‘They Both Die at The End’ by Adam Silvera - Muhammad Al Fatih Mahyuzar; Rini Susanti Wulandari (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This study aims to explore the representation of death and its influence on human behavior in Adam Silvera's novel They Both Die at the End through Sigmund Freud's psychoanalytic approach. In the novel, the call of the "Death-Cast", which informs people of their last day, functions as a trigger for the primacy of death, a condition that increases existential anxiety and psychological tension. This study uses qualitative methods to examine the responses of two main characters, Mateo and Rufus, to the certainty of death they face by examining the dynamics of the id, ego, and superego. In addition, the study also highlights how defense mechanisms such as repression, rationalization, and sublimation are used by both characters as a way to deal with emotional stress. The findings show that awareness of death drives significant psychological changes, such as Mateo, who was initially introverted but developed into a more open and honest person with himself, while Rufus experienced a shift from impulsive and aggressive attitudes to deeper self-understanding and warmer relationships. This transformation reflects the inner conflict between unconscious drives, moral values, and the role of the ego in mediating the two.